Association of lactate to albumin ratio with short-term and long-term mortality in critically ill patients with heart failure complicated by sepsis: a retrospective study using the MIMIC-IV database - Wu, Yuming; Wang, Ling; Wen, Qiuyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundElevated lactate to albumin ratio (LAR) has been associated with poor prognosis in critical illnesses. However, evidence regarding LAR in patients with heart failure (HF) complicated by sepsis remains limited. This study aimed to explore the relationship between LAR and both short-term and long-term mortality in this population.MethodPatient data were extracted from the Medical Information Mart for Intensive Care (MIMIC-IV) database and stratified into quartiles based on LAR. The primary endpoints were 28-day and 365-day all-cause mortality. Kaplan–Meier survival analysis was performed to compare outcomes across the four groups. Association between LAR and mortality was assessed using restricted cubic splines (RCS) and Cox regression analysis. Additionally, subgroup and sensitivity analyses were conducted.ResultAmong 4,242 participants (mean age 72.04 ± 13.50 years; 57.33% male), Kaplan–Meier analysis showed that higher LAR levels were associated with increased 28-day and 365-day all-cause mortality (log-rank P < 0.001). Cox regression analysis confirmed that elevated LAR was independently associated with higher 28-day and 365-day all-cause mortality (HR: 1.101, 95% CI 1.005–1.205; HR: 1.125, 95% CI 1.039–1.218). The highest LAR quartile (>0.97) remained significantly associated with both 28-day and 365-day mortality (Q4 vs. Q1: HR: 1.313, 95% CI 1.063–1.622; HR: 1.310, 95% CI 1.092–1.571). RCS analysis indicated a linear positive correlation between LAR and mortality (P for nonlinear > 0.05). Subgroup analysis revealed a significant interaction with hypertension (P for interaction = 0.033 for 28-day; P for interaction = 0.015 for 365-day). Sensitivity analyses confirmed the robustness of these findings.ConclusionIn critically ill patients with HF complicated by sepsis, LAR is a reliable and independent predictor of mortality. Patients in the highest LAR quartile (>0.97) have a significantly increased risk of death, providing a clinically useful reference for rapid identification of high-risk individuals. The significant interaction observed in hypertensive subgroups highlights the need for heightened clinical attention. Overall, LAR may serve as a practical biomarker for risk stratification and prognostic evaluation in this vulnerable population.